Citizenship and values education in post-genocide Rwanda: an analysis of the Itorero training scheme for high school leavers - Nzahabwanayo, Sylvestre (My University, 2016)
This research investigates the citizenship and values education notions at work in the Itorero training scheme for high school leavers (HSLs) in post-genocide Rwanda. It establishes the attitudes of HSLs and trainers towards this scheme. The thesis contributes to the existing literature on citizenship and values education in post-genocide countries, on the use of indigenous programs of citizenship education, and on the contextual framework of citizenship and values education. The methodology guiding this thesis is a mixed-method design; it is both quantitative and qualitative. In terms of conceptual framework, citizenship and values education models are applied to the analysis of the scheme in order to establish a model deemed preferable to competing models. In relation to citizenship education, the thesis engages with the civic republican, liberal, communitarian, cosmopolitan and radical democratic notions, with the main aim of determining the extent to which these notions inspire the Itorero training scheme. With regard to values education, the study engages with character education, care ethics, cognitive moral development approach and values clarification, and attempts to establish the extent to which these values education notions inform the Itorero training for HSLs. The thesis reveals that the Itorero training is committed robustly to the civic republican and communitarian notions of citizenship. While there is nothing inherently wrong with the civic virtues emphasized by these concepts (e.g. self-sacrifice, courage, patriotism, connectedness, and common good concern), I argue that the civic republican/communitarian paradigm, as practiced in post-genocide Rwanda, runs the risk of reducing „good citizenship‟ to blind patriotism, unqualified loyalty and uncritical obedience to the ruling party. It is suggested that the civic republican and communitarian notions be replaced by the „critical-democratic-cosmopolitan‟ notion of citizenship. Concerning values education, the thesis shows that the Itorero training relies heavily on character education. Though this approach allows HSLs to be conversant with values and taboos of the Rwandan culture, I argue that the overreliance on character education raises serious concerns. This is the case, particularly because some studies (e.g. Arthur, 2008; Boyd, 2010; Kohn, 1997; Liu, 2014) have found character education deficient mainly in two ways: first, it is perceived as „indoctrination‟; second, it is not deemed sustainable. It is not clear from the present study how the Itorero training scheme addresses these limitations pertaining to character education. Therefore, there are strong reasons to believe that the Itorero training for HSLs runs the risk of simply being a „bag of virtues approach‟ or a „fix-the-kid approach‟. The thesis recommends engaging with other approaches such as care ethics, cognitive-developmental approach and values clarification. It is also suggested that the distinction between citizenship and character education should be maintained, or rather reintroduced. In short, the thesis suggests a new model for citizenship and values education in post-genocide Rwanda. The thesis demonstrates that, according to HSLs, the quality of trainers, the content, and the training environement constitute best predictors of the success of the Itorero training scheme for HSLs. The thesis indicates, however, that HSLs seem displeased with the quality of trainers, chiefly because of the presence of sexual abuse and harsh forms of corporal punishment on some training sites. Hence, the thesis shows that it is important to recruit experienced, mature and morally blameless trainers. The findings of this study show that, according to trainers, HSLs‟ motivation and prerequisites constitute best predictors of the success of the Itorero training scheme. Yet the thesis demonstrates that there are serious problems affecting both the motivation and prerequisites of HSLs. The motivation is negatively affected by the lack of enforcement mechanisms to make the attendance to Itorero training compulsory. In reference to prerequisites, the study notes that while HSLs have the requisite epistemological tools to grasp Itorero teaching, their parents indoctrinate them with ethnocentric and xenophobic ideas, which affects the assimilation process of the Itorero teaching, particularly with regard to the unity of Rwandans. In order to increase the motivation of HSLs, the study recommends that the certificate issued at the end of Itorero training be part of required documents for HSLs to enroll either in public or private institutions of higher learning in Rwanda. As to HSLs‟ prerequisites, the present study suggests that organizing and reinforcing Itorero for parents at the village level [Umudugudu] be considered as a matter of immediate urgency.
A Thesis submitted to the Wits School of Education, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2016
Keywords: Education and state--Rwanda; Citizenship--Study and teaching--Rwanda